Thrombocytopenia in Cases Presenting with Chronic Liver Disease Due to Hepatitis C Virus - Anoosh Qayyum, Adeel Khalid Choudhary, Maheen Altaf, Sarwat Iqbal, Aqsa Noureen, Saima Rasheed (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: record the rate of thrombocytopenia in cases presenting with chronic liver disease(CLD) due to Hepatitis C virus. Methodology: A total of 300 patients who were diagnosed with CLD caused by HCV and were over the age of 18 were part of this trial. The enroleld cases were admitted from Deptt. of Medicine, Rawalpindi Medical University. All patients diagnosed using AST, ALT levels of liver function test and reported by the radiologist was labeled as havign CLD. A thrombocyte count and an ELISA test for HCV were performed on the blood sample that was supplied to the laboratory from patients who had been diagnosed with CLD to determine presence/absence of thrombocytopenia. Results: Patients were in majority in age group 41-60 yrs i.e. 62%(n=186), mean age 42.63+8.57 yrs, 60 percent males (n=180) and there are 40 percent female subjects (n=120). Thrombocytopenia was found in 26 percent of CLD patients (n=78), while 74 percent of CLD patients (n=222) did not have any signs of thrombocytopenia. Conclusion: Higher rate of thrombocytopenia was observed in CLD cases due to hepatitis C virus. It needs attention for its early detection and management.